Misinformation encountered during a simulated jury deliberation can distort jurors´ memory of a trial and bias their verdicts - Thorley, Craig (Legal and criminological psychology, 2020)
PURPOSE-Jurors swear to base their verdicts solely on the evidence presented at trial. Their recall of a trial during deliberation can, however, be inaccurate, exposing other jurors to misinformation about the trial. This study examined whether jurors who are exposed to misinformation during a simulated deliberation, where the misinformation supports the prosecution's case, will misremember the misinformation as appearing during a trial and be more likely to reach a guilty verdict. It also examined whether allowing jurors to take notes during a trial, and refer to those notes throughout, stops these potentially harmful effects.METHODS-One hundred and twenty-four participant jurors watched a murder trial. Half were allowed to take notes. They then read a transcript of a deliberation that either contained or did not contain six pieces of pro-prosecution misinformation. Afterwards, they reached a verdict. Finally, they completed a source monitoring test that required indicating whether the misinformation, and actual trial information, appeared during the trial.RESULTS-Jurors exposed to misinformation misremembered it as appearing during the trial. Those who misattributed the most misinformation to the trial were most likely to reach a guilty verdict. Note taking, and note access, did not stop these effects.CONCLUSIONS-Jurors can make mistakes when recalling a trial during deliberation but the consequences of this were largely unknown. This study provides initial evidence that their mistakes may distort other jurors' recollection of the trial and bias their verdicts. Attempts to replicate these findings using live deliberations are encouraged to determine their generalizability.